Concurrent Effects of Sediment Accretion and Nutrient Availability on the Clonal Growth Strategy of Carex brevicuspis-A Wetland Sedge That Produces Both Spreading and Clumping Ramets - Chen, Xinsheng; Liao, Yulin; Xie, Yonghong; Li, Feng; Deng, Zhengmiao; Hou, Zhiyong; Wu, Chao (Frontiers in Plant Science, 2017)
Clonal plants producing both clumping and spreading ramets can adjust their growth forms in response to resource heterogeneity or environmental stress. They might produce clumping ramets to retain favorable patches, or produce spreading ramets to escape from stress-affected patches. This study aimed to investigate the rarely reported concurrent effects of sediment accretion and nutrient enrichment, which often occur simultaneously in lacustrine wetlands, on the vegetative propagation and clonal growth forms of Carex brevicuspis C.B. Clarke by conducting a factorial experiment of sediment burial and nutrient addition. Biomass accumulation, new ramet and rhizome numbers, and ramet length of C. brevicuspis were not affected at moderate burial, but were significantly lower after deep burial. Similarly, nutrient enrichment increased the growth and vegetative propagation of C. brevicuspis up to moderate sediment burial, but not after deep burial. Sediment accretion increased the proportion of spreading ramets produced by C. brevicuspis, whereas nutrient addition had no effect on the clonal growth forms. Our results indicated that the plasticity of clonal growth forms is an effective strategy used by plants to acclimate to moderate sediment accretion. Nutrient enrichment did not influence the clonal growth forms of C. brevicuspis and could not facilitate its acclimation to heavy sedimentation condition.